Re-examination of 1- vs. 3-Sets of Resistance Exercise for Pre-spaceflight Muscle Conditioning: A Systematic Review and Meta-Analysis - Ralston, Grant W.; Kilgore, Lon; Wyatt, Frank B.; Dutheil, Frédéric; Jaekel, Patrick; Buchan, Duncan S.; Baker, Julien S. (Frontiers in Physiology, 2019)
Background: Recommendations on resistance training (RT) set-volume protocols in preparation for spaceflight muscular strength conditioning remains equivocal. A meta-analysis was performed on the effects of single-set (S), or three-set (M3) RT on muscular strength per exercise for different body segments and joint types (multi-joint and single-joint). Methods: Computerized searches were performed on PubMed, MEDLINE and SPORTDiscus™. Twelve studies were considered appropriate according to pre-set eligibility criteria. Outcomes analyzed were pre-to-post-muscular strength change on; multi-joint and single-joint combined; upper body only; lower body only; multi-joint exercises only; single-joint exercises only. Results: Upper body exercise analysis on combined subjects and untrained subjects only reported greater but not significant strength gains with M3 (ES 0.37; 95% CI 0.09–0.82; P = 0.11 and ES 0.35; 95% CI−0.49 to 1.19; P = 0.42). Trained only subjects reported superior strength gains with M3 (ES 0.63; 95% CI 0.34–0.92; P = <0.0001). Lower body exercise on combined subjects and untrained subjects only reported superior strength gains with M3 (ES 0.35; 95% CI 0.10–0.60; P = 0.006 and ES 0.49; 95% CI 0.14–0.83; P = 0.005). Trained subjects only observed greater but not significant strength gains with M3 (ES 0.18; 95% CI −0.23 to 0.58; P = 0.39). Multi-joint exercise on combined subjects reported greater strength gains with M3 (ES 0.83; 95% CI 0.14–1.51; P = 0.02). Trained only subjects reported greater strength gains with M3 (ES 0.52; 95% CI 0.10–0.94; P = 0.02). Single-joint exercise on combined subjects and untrained only observed greater strength gains for M3 (ES 0.49; 95% CI 0.26–0.72; P = <0.0001 and ES 0.56; 95% CI 0.21–0.91; P = 0.002). Trained only subjects reported greater but not significant strength gains with M3 (ES 0.37; 95% CI −0.01 to 0.75; P = 0.06). Conclusion: For astronauts in space-flight preparation, the findings suggest that M3 training appears to be preferable over S for developing muscular strength. Nevertheless, depending on the physical conditioning of the crew member or tight pre-flight scheduling, S is still able to provide a positive strength training stimulus.